Diagnosis and Management of Giant Hepatic Hemangioma: The Usefulness of Contrast-Enhanced Ultrasonography. (16th May 2013) - Maruyama, Masaki; Isokawa, Osamu; Hoshiyama, Koki; Hoshiyama, Ayako; Hoshiyama, Mari; Hoshiyama, Yoshihiro
Abstract : Giant hepatic hemangiomas, though often asymptomatic, may require intervention if rapid growth occurs. The imaging studies including the computed tomography, magnetic resonance imaging, and ultrasonography, and so on are effective for the diagnosis and the management of this tumor; however, due to its size and various patterns of these studies, we need to carefully consider the therapeutic methods. Compared to the cost needed for these modalities, recently developed and approved Perflubutane- (Sonazoid-) based contrast agent enhanced ultrasonography is reasonable and safe. The major advantage is the real-time observation of the vascular structure and function of the Kupffer cells. By this procedure, we can carefully follow the tumor growth or character change in a hemangioma and decide the timing of therapeutic intervention, since abdominal pain, abdominal mass, consumptive coagulopathy, and hemangioma growth are the signs for the therapeutic intervention. We reviewed recent reports about Sonazoid-based enhancement and also showed the representative images collected in our department. This is the first review showing the detailed findings of the giant hemangiomas using Perflubutane (Sonazoid). This review will help the physician in making the decision, and we hope that Sonazoid will gain widespread acceptance in the near future.